Suara Naratif dalam Na Willa Karya Reda Gaudiamo: Perspektif Naratologi Gerard Genette - Zahro, Alhasanah; Indrastuti, Novi Siti Kussuji (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
In the children's novel Na Willa, there are significant differences in narrative development compared to children's stories in general. The difference is seen in the approach to the delivery of advice, teachings, and morals. In Na Willa the narrative is still present, but not as the purpose of the story. This study aims to find the narrative voice and reveal its function in Na Willa's novel. The research results identify three categories of narrative voice in this novel, including 1) storytelling time with subsequent, prior, simultaneous, and interpolated techniques, 2) narrator techniques using homodiegetic and autodiegetic narrators, and 3) narrative level at extradiegetic-homodiegetic. The findings conclude that the function of narrative voice in the novel is not only as a tool to convey the story, but also to build emotional closeness with the reader. The approach of using children's point of view or perspective as the narrator and main character allows child readers to feel more connected and enjoy the story more freely and creatively.